1988
DOI: 10.1159/000120409
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Neuropathology of Proliferative Vasculopathy and Hydranencephaly-Hydrocephaly with Multiple Limb Pterygia

Abstract: We describe the third family in which fetuses have very narrow cerebral cortical mantles, enlarged ventricles, a peculiar proliferation of cerebral cortical arteries, and hypoplasia of muscle. We describe the youngest fetus yet reported. Previously this condition was interpreted as destructive, perhaps due to infection. We believe it is a primary failure of neuroectodermal cells to form in the ventricular zone with too few resulting cells in cerebral cortex and that the abnormal vascular proliferation is part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 5 publications
7
24
0
Order By: Relevance
“…Cleft palate and pterygia of large joints were observed at termination. Norman and McGillivray (1988) reported a similar single case.…”
Section: Hydranencephaly Calcification Of Basal Ganglion and Prolifmentioning
confidence: 85%
“…Cleft palate and pterygia of large joints were observed at termination. Norman and McGillivray (1988) reported a similar single case.…”
Section: Hydranencephaly Calcification Of Basal Ganglion and Prolifmentioning
confidence: 85%
“…In 1988, Norman and McGillivray reported two new cases in the third family so far described, where the most obvious signs were hydrocephaly, polyhydramnios, and multiple pterygia of the limbs 3 . Moreover, these authors regarded the case reported by Mbakop et al 4 in 1986 as another case of PVHH syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Norman and McGillivray suggested that disorders of neuronal migration could be involved as seen in Walker-Warburg syndrome and Fukuyama congenital muscular dystrophy 3 . Harding et al suggested that the abnormal proliferative vasculopathy in the nervous tissue might play the main part in the pathogenesis observed as early as in the first trimester 5 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations